FLT3/D835Y mutation knock-in mice display less aggressive disease compared with FLT3/internal tandem duplication (ITD) mice - Bailey, Emily (National Academy of Sciences, 2013)
FMS-like tyrosine kinase 3 (FLT3) is mutated in approximately one third of acute myeloid leukemia cases. The most common FLT3 mutations in acute myeloid leukemia are internal tandem duplication (ITD) mutations in the juxtamembrane domain (23%) and point mutations in the tyrosine kinase domain (10%). The mutation substituting the aspartic acid at position 838 (equivalent to the human aspartic acid residue at position 835) with a tyrosine (referred to as FLT3/D835Y hereafter) is the most frequent kinase domain mutation, converting aspartic acid to tyrosine. Although both of these mutations constitutively activate FLT3, patients with an ITD mutation have a significantly poorer prognosis. To elucidate the mechanisms behind this prognostic difference, we have generated a knock-in mouse model with a D838Y point mutation in FLT3 that corresponds to the FLT3/D835Y mutation described in humans. Compared with FLT3/ITD knock-in mice, the FLT3/D835Y knock-in mice survive significantly longer. The majority of these mice develop myeloproliferative neoplasms with a less-aggressive phenotype. In addition, FLT3/D835Y mice have distinct hematopoietic development patterns. Unlike the tremendous depletion of the hematopoietic stem cell compartment we have observed in FLT3/ITD mice, FLT3/D835Y mutant mice are not depleted in hematopoietic stem cells. Further comparisons of these FLT3/D835Y knock-in mice with FLT3/ITD mice should provide an ideal platform for dissecting the molecular mechanisms that underlie the prognostic differences between the two different types of FLT3 mutations.